Revalidation of Proactive Gastrostomy Tube Placement Guidelines for Head and Neck Cancer Patients Receiving Helical Intensity-Modulated Radiotherapy - Teresa E. Brown; Angela Byrnes; Aaron C. Chan; Kathleen Dwyer; Anna Edwards; Claire L. Blake; Merrilyn D. Banks; Brett G. M. Hughes; Charles Y. Lin; Lizbeth M. Kenny; Ann-Louise Spurgin; Judith D. Bauer (Current Oncology)
The Royal Brisbane and Women’s Hospital (RBWH) Swallowing and Nutrition Management Guidelines for Patients with Head and Neck Cancer were developed to enable evidence-based decision-making by the Head and Neck Multidisciplinary Team (H&N MDT) regarding enteral nutrition support options. The purpose of this study was to revalidate these guidelines in a cohort of patients receiving helical intensity-modulated radiotherapy (H-IMRT) compared to a historical cohort who received primarily 3D-conformal radiotherapy. Eligible patients attending the RBWH H&N MDT between 2013 and 2014 (n = 315) were assessed by the guidelines, with high-risk patients being recommended proactive gastrostomy tube placement. Data were collected on guideline adherence, gastrostomy tube insertions, the duration of enteral tube use and weight change. Sensitivity, specificity and positive predictive and negative predictive values were calculated and compared with the historical cohort. Overall guideline adherence was 84%, with 60% and 96% adherence to the high-risk and low-risk pathways, respectively. Seventy patients underwent proactive gastrostomy tube placement (n = 62 high-risk; n = 8 low-risk). Validation outcomes were sensitivity 73% (compared to 72%) and specificity 86% (compared to 96%). The guidelines yielded a high sensitivity and specificity, remaining valid in a cohort of patients treated with H-IMRT. Further studies are recommended to improve the sensitivity and understand the decrease in specificity in order to make ongoing guideline improvements.